Etika Terapan Dalam Misi Global - Martina Novalina; Hasiholan Sihaloho; Mario Alberto Manodohon (Sekola Tinggi Teologi Sangkakala Jakarta, 2020)
Awareness of the realities of challenges in the world of mission arises because of the many developing global issues. How to respond correctly to these challenges is regulated in an applied ethics. This article aims to look at the role of applied ethics in global missions and produce a finding of the attitudes that Christian missioners should take. The method used is qualitative research with a literature review. The result is that in relation to applied ethics, a holistic mission does not merely pursue soul winning as the end of the Christian life. On the contrary, the commissioning to make them My disciples according to Christian ethics necessitates a process of transformation; on the one hand self-transformation and on the other social transformation. Mission must be accompanied by the application of the correct Christian ethics, so that every behavior that is created shows the face of Christ himself. AbstrakKesadaran akan realitas tantangan di tengah dunia misi muncul karena banyaknya isu-isu global yang berkembang. Bagaimana meresponi dengan benar tantangan tersebut diatur dalam sebuah etika terapan. Artikel ini bertujuan untuk melihat peran etika terapan dalam misi global dan menghasilkan sebuah temuan sikap yang harus dilakukan oleh penggiat misi Kristen. Metode yang digunakan adalah penelitian kualitatif dengan literature review. Hasil yang didapat adalah bahwa dalam hubungan dengan etika terapan, misi yang holistik tidak sekedar mengejar pemenangan jiwa sebagai akhir dari kehidupan Kristen. Sebaliknya, pengutusan untuk menjadikan mereka murid-Ku sesuai dengan etika Kristen mengharuskan suatu proses transformasi; di satu pihak transformasi diri dan di pihak yang lain transformasi sosial. Misi harus disertai dengan penerapan etika Kristen yang benar, sehingga setiap perilaku yang tercipta menampilkan wajah Kristus itu sendiri.